Protection of Muslim Consumers In Covid-19 Vaccination (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
In Indonesia, the Covid-19 pandemic has caused a large number of deaths, and the number of Covid-19 patients continues to rise dramatically. In accordance with the Health Quarantine Act, it is the responsibility of the state to offer protection during public health emergencies so as to prevent the spread of health risks. According to the Consumer Protection Act, one of the state's responsibilities is to provide Covid-19 vaccines to the community, which is referred to as consumers (end users). Similarly, consumers have the right to acquire information about the Covid-19 vaccination prior to its usage, including information about the vaccine's halal status. As the Halal Product Guarantee Law mandates halal information for all items circulating on Indonesian territory, halal information is mandatory. This study seeks to examine the legislation of Muslim consumer protection in order to acquire halal information regarding Covid-19 immunization. In accordance with its aims and in order to get these answers, this article uses the juridico-normative technique to investigate the depth of the concepts behind the rules governing Muslim consumer protection in Covid-19 immunization, utilizing secondary data sources and a statute approach. This report states that the government has not mandated halal information for Covid-19 immunizations administered to Muslim customers. Finally, this article advises harmonizing Covid-19 vaccination policies in order to increase the control of misleading information in the administration of Covid-19 immunizations to Muslim consumers.